THE SENTENCE AS A UNIT OF SYNTAX IN ENGLISH: STRUCTURE AND TYPES - Nazokat Inoyatulloyeva Izzatullo qizi (TADQIQOTLAR, 2026)
Annotation This paper explores the sentence as a fundamental unit of syntax in English, with a particular focus on the differences between spoken and written sentence structures. The study highlights how spoken language tends to be more spontaneous, less structured, and context-dependent, often characterized by ellipsis, coordination, and the use of fillers. In contrast, written language is presented as more formal, organized, and precise, relying on complex sentence constructions, subordination, and punctuation for clarity. The paper emphasizes the role of the sentence in conveying meaning, structuring thought, and fulfilling communicative purposes across different modes of language use. It concludes that understanding sentence structure enhances both linguistic competence and effective communication, demonstrating the importance of syntax in expressing ideas clearly and accurately.